Micro pump using shape memory alloy thin films - Charlie, Eric. (2009)
The advance of microsystems has made micropump, as one of the most important components in microsystems, received a lot of attention in research and development. Micropump can be actuated by various mechanisms, such as electrostatic, piezoelectric, electromagnetic and shape memory alloy thin film.